2020
DOI: 10.1007/s10964-020-01308-9
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Associations between Popularity, Popularity Goal, and Aggression, Alcohol Use and Prosocial Behaviors in Adolescence: A 3-Year Prospective Longitudinal Study

Abstract: Adolescents' popularity and popularity goal have been shown to be related to their aggression and alcohol use. As intervention efforts increasingly aim to focus on prosocial alternatives for youth to gain status, it is essential to have a comprehensive understanding of how popularity and popularity goal are associated with aggression and substance use as well as prosocial behaviors over time. The current study examined the bidirectional associations of aggression (overt and relational aggression), alcohol use,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 49 publications
1
24
0
1
Order By: Relevance
“…Popularity motivations have been found to be precursors to a range of antisocial or problematic adolescent outcomes, including maladaptive social media use (i.e., sexting, mobile porn use or sexual grooming; Vanden Abeele et al, 2014 ; Utz et al, 2012 ). Longitudinal research indicated increased risk of unhealthy behaviors including alcohol use amongst those with high need for popularity (Malamut et al, 2020 ). The drive for popularity may motivate a range of risky behaviors among adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Popularity motivations have been found to be precursors to a range of antisocial or problematic adolescent outcomes, including maladaptive social media use (i.e., sexting, mobile porn use or sexual grooming; Vanden Abeele et al, 2014 ; Utz et al, 2012 ). Longitudinal research indicated increased risk of unhealthy behaviors including alcohol use amongst those with high need for popularity (Malamut et al, 2020 ). The drive for popularity may motivate a range of risky behaviors among adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…More tellingly, a two-wave study with Canadian students in grades 9–11 found that social aggression predicted significant increases in need for popularity assessed five months later (Dumas et al, 2019 ). However, a three-year prospective study found no such relationship between popularity goals and overall aggression, nor did popularity goals predict increased relational aggression (Malamut et al, 2020 ). To date, these studies have not examined bullying per se.…”
Section: Introductionmentioning
confidence: 99%
“…Descriptive norms influence adolescents' alcohol use and smoking behavior (Borsari & Carey, 2001;Veenstra et al, 2018). Popular adolescents have a strong impact on classroom norms; they decide who is accepted, who fits in, or who is rejected (Malamut et al, 2020;Veenstra et al, 2018), and their behaviors pose an important norm to others (Dijkstra & Gest, 2015). Not conforming to classroom norms can lead to social sanctions such as rejection or exclusion (e.g., social misfit theory, cf.…”
Section: Popularity Norms As Explanation For Educational Differences In Risk Behaviormentioning
confidence: 99%
“…Alcohol dependence (AD) is a common psychiatric disorder and is characterized by loss of control over alcohol drinking, which is associated with impaired decision-making, seeking alcohol regardless of health status and behavioral impairments such as aggression and impulsivity, even suicide attempts ( Tobore, 2019 ; Witkiewitz et al, 2019 ). Pieces of evidence suggested that AD was a multifactorial and genetic disease, and the pathogenesis of AD included neurobiological, genetic and epigenetic, psychological, social, and environmental factors ( Kiive et al, 2017 ; Newman et al, 2018 ; Malamut et al, 2021 ). Some patients with AD recover after lifestyle modifications in the absence of medical treatment, while many of them relapse and display damaged brain structure and function ( Grant et al, 2015 ; Abrahao et al, 2017 ; Erickson et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%